Estabilidade atmosférica em projetos eólicos: estimativa bayesiana do comprimento de Monin Obukhov e simulação do escoamento atmosférico - Ramos, Daniel Agnese (2017)
This dissertation managed to increase the reliability of the assessment of any wind energy project using only what is already standard for any wind project development. Bayesian estimates of atmospheric parameters using only average wind speed measurements of a cup anemometer and CFD simulations coupled with thermal equations are used in order to define a more consistent WRG database without acquiring more data, investment or computational demand. Moreover, postprocessing of such WRG database aiming to kinetically identify vortexes was also carried out. Some validation studies were carried out in order to prove the reliability of those new methodologies created within this research. Results of atmospheric flow simulations regarding thermal stability are presented and contrasted with similar results that do not take into consideration thermal stability. Thus, the final analysis of the results obtained herein shows beyond doubt that it is possible to increase the quality of a standard wind resource assessment without necessarily requiring further investments or increasing computational demand.